Bioprospecção de fungos termofílicos produtores de -glicosidases: potencial de produção de Aspergillus fumigatus - Ratuchne, Aline (2019)
The screening of thermophilic filamentous fungi with possible potential for the production of enzymes of industrial interest has increased in recent years. Furthermore, these studies help to understand the microbial diversity and can elucidate issues related to the evolution and dispersion of these microorganisms in the habitat. Among the enzymes of biotechnological relevance, β-glucosidases stand out for their use in sectors such as bioethanol production, improvement of beverage aroma and in the pharmaceutical industry. This work aimed to isolate thermophilic fungal linage from the soil and litter of two remnants of Araucaria Forest from the Central-South region of Parana. The objective was also to evaluate the potential of βglucosidases production by the fungi obtained, as well as to identify molecularly the optimum producing lineage. In addition, the effects of various physico-chemical parameters on the production of β-glucosidases by the previously selected production linages were investigated, using canola meal as an alternative substrate. Finally, the enzymes produced were biochemically characterized. Between the two isolated linages, one of each area and both of soil samples, the one with the highest levels of β-glucosidases production, when cultivated in the presence of canola meal, was molecularly identified as Aspergillus fumigatus and based on the growth characteristics presented under different temperatures, this lineage was classified as thermotolerant. The highest levels of production were reached with the concentration of 2.9% of substrate, pH of the environment adjusted to 4.2 in 101 hours of culture, corresponding to 24.53 U mL-1. The β-glucosidases produced were more active at 80 °C, with a pH of 5.5. When evaluating the effect of metal ions and other substances on β-glucosidase activity, the enzyme was activated by Mn2+ and Cu2+ at 10 mM, and it was strongly inhibited by the addition of 10 mM of Hg2+ and SDS. Canola meal proved to be a promising substrate for the production of βglucosidases, being a residue with high availability and low cost. The thermophilic fungus A. fumigatus demonstrated great potential for the production of β-glucosidases, which presented desirable properties for most industrial applications, especially its optimum activity at 80 ºC.